O-024 Medicare Underpayment is a Major Cause of Deficit in Endovascular Treatment of Aneurysms. (26th July 2014) - Rai, A; Tarabishy, A; Cline, B; Patterson, J; Boo, S; Carpenter, J
Abstract : Background: Coiling remains the current primary therapy for aneurysms. Understanding the economics of coiling will establish a framework against which the financial impact of future devices may be measured. Methodology: A retrospective analysis of 542 aneurysm coilings was performed. Of these, financial-data was available on 377 patients. This included the DRG-code, hospital charges, total-cost, implant-cost, payments received, the payer and the length of stay for each admission. Treatment parameters included aneurysm size, type and number of coils, and use of adjunctive devices. We hypothesised that aneurysm size, rupture-status, number of coils and adjunctive devices would impact the financial outcome. Results: 235(62.3%) aneurysms were treated electively while 142(37.7%) were ruptured. The length of stay was 2.5(±5) days for elective and 17.7(±13) days for ruptured aneurysms (p < 0.0001). Coiling alone was performed in 244(64.7%), stent-coiling in 100(26.5%), balloon-coiling in 30(8%) and stenting only in 3(0.08%) patients. There were 183(48.5%) aneurysms in the 6–11 mm size group, 148(39.3%) in the <6 mm group and 46(12.2%) in the >11 mm group. The number of coils/aneurysm was 4.1(±2.8) for the <6 mm-group, 6.7(±3.8) for the 6–11 mm-group and 11.6(±7.4) for the >11 mm-group, (p < 0.0001). The hospital charges were 112, 050(±93690), total-cost 56, 760(±46653), implant-cost 11, 417(±7638) and payments 50, 636(±58026). Overall, the hospital lost 5858 (±43456) per treatment. The mean payments by payer (Figure 1 ) and the difference between total-cost and payments by payer (Figure 2 ) show that apart from Blue Cross/Blue Shield and Commercial insurance, every other payer averaged a net loss-for the hospital. There was no impact of the rupture status, age, gender, aneurysm size, use of adjunctive device on the net deficit to the hospital. Conclusion: In our Medicare/Medicaid heavy population, the payer-mix was an overwhelmingly significant financial determinant in aneurysm treatment. Contrary to our hypothesis, none of the other factors impacted the average net deficit that the hospital suffered in these cases. Disclosures: A. Rai: 2; C; Stryker Neurovascular, Codman Neuro. A. Tarabishy: None. B. Cline: None. J. Patterson: None. S. Boo: None. J. Carpenter: None.